Mid-aortic syndrome presented as dilated cardiomyopathy - Kah, Yit Pang; Yubbu, Putri; Ali, Norliza; Ghee, Tiong Koh (BMJ Publishing Group, 2024)
Mid-aortic syndrome (MAS) is a rare vascular disease that usually leads to renovascular hypertension. With the predominant manifestations being intractable arterial hypertension and lower extremity arterial insufficiency, it has rarely been associated with dilated cardiomyopathy. We report a young girl with congestive heart failure, where the cause was initially attributed to dilated cardiomyopathy. A repeated echocardiogram 6 months later brought the physician's suspicion of MAS because of the abnormal colour of Doppler from the subcostal view. Further assessment using CT angiography revealed discrete thoracic coarctation at the level of T10, with the narrowest diameter of 2.1 mm, thus confirming the diagnosis. Her inflammatory markers and connective tissue screening were negative. She underwent successful stenting of coarctation of the aorta, which later caused improvement in her cardiac function. We highlighted the importance of looking for treatable causes of dilated cardiomyopathy and vigilant clinical and echocardiogram assessment with high suspicion to diagnose MAS.